Geographical and temporal variation in the diet of Bank Cormorants Phalacrocorax neglectus in South Africa. (13th December 2019) - Dyer, BM; Cooper, J; Crawford, RJM; Sherley, RB; Somhlaba, S; Cockcroft, A; Upfold, L; Makhado, AB
Abstract : The Bank Cormorant Phalacrocorax neglectus is endemic to the Benguela upwelling ecosystem off southwest Africa and is classified as Endangered owing to a recent large reduction in its number. It is thought that food scarcity, including a decreased abundance of West Coast rock lobster Jasus lalandii, has been a major driver of the decrease, yet its diet in South Africa is poorly known. We collected 941 pellets regurgitated by Bank Cormorants, at 18 South African breeding colonies during 1975–1985, and 1 523 pellets at 17 colonies during 1995–2002. The species composition of the diet (% numbers) was significantly different between the two periods, with widespread decreases in proportions of rock lobster in the west and of octopus and cuttlefish Sepia spp. at most localities. These taxa were replaced in the diet by fish, including Gobiidae and Clinidae. The pelagic goby Sufflogobius bibarbatus, an important prey of Bank Cormorants in Namibia, was absent from pellets collected in 1975–1985 but common at northern localities from 1995–2002. Composition of the diet by frequency of occurrence was only determined for 1995–2002, when rock lobster was present in 67% of all samples collected, cuttlefish in 39%, and Clinidae in 32%. Data for 1975–1985 and 1995–2002 showed that carapace lengths of rock lobsters eaten by Bank Cormorants averaged 56 mm (range 22–82 mm) and 50 mm (range 22–75 mm), respectively, which compares to the minimum legal size of 75 mm for fisheries in South Africa. This energy- rich prey item was an important constituent of the diet in the winter breeding period.